Six Sigma untuk Peningkatan Kualitas Sajian Makanan Dine-In: Studi Kasus Usaha Makanan dan Minuman di Indonesia - Arry Rahmawan Destyanto; Melinda Nurimannisa (Universitas Islam Raden Rahmat, Malang, 2024)
This research proposes the Six Sigma Framework as a tool to drive operational excellence in non-manufacturing businesses, especially the food and beverage industry through a real case study to improve the quality of dine-in meals. Six Sigma's Define, Measure, Analyze, Improve, and Control (DMAIC) approach was applied to identify the root causes of the problem and formulate effective solutions for the improvement of serving quality. The implementation results showed significant improvement in Dine-In serving quality by reducing serving defects by 62.5% compared to the condition before Six Sigma implementation. This research fills a critical gap in the literature by providing actionable recommendations for applying Six Sigma in a non-manufacturing context, specifically to improve Dine-In serving quality in the food and beverage industry that can be used as a reference for many related industry players in Indonesia.